On the use of non traditional stacking to maximize critical buckling loads in flat composite panels. (1st April 2021) - Vijayachandran, Avinkrishnan; Waas, Anthony
Abstract: Traditional lay-ups in laminated composite structural parts have largely focused on using quasi-isotropic laminates made of permutations of 0 °, 90 ° and ± 45 ° laminae. These laminates are referred to as legacy quad laminates (LQL). In this study, three different lay-ups of symmetric laminates to compute critical buckling loads under uniaxial in-plane compressive loads is first investigated. An optimization problem is solved to determine the lay-ups that maximize the buckling performance. The resulting laminates are compared against a new class of laminates, referred to as double-double (DD), which have distinctive advantages for thickness tapering and therefore manufacturability. Both, symmetric and unsymmetric DD laminates are studied, while in the latter case, a thermal cure cycle followed by the application of in-plane loads is used to determine the structural performance in compression. To further verify the versatility of DD laminates, biaxial buckling loads are computed for quad, DD and optimized lay-ups. It is concluded that DD laminates, because of their manufacturability advantages, are promising candidates for several aerostructural applications.